2020
DOI: 10.1016/j.gore.2020.100643
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of endometrial cancer symptoms among overweight and obese women presenting to a multidisciplinary weight management center

Abstract: Highlights 44% of overweight or obese women reported abnormal bleeding symptoms associated with endometrial cancer (EC). Many obese women have not talked to their providers about these symptoms. Gynecologists should collaborate with providers of obese women to facilitate prevention and early detection of EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Beavis, AL et al (2020) 6 showed low levels of awareness of EH/EC symptoms and low perceived risk may contribute to the low reporting of symptoms. In a study of women presenting for bariatric surgery, half perceived their personal risk of developing uterine cancer as "not likely" or "not possible".…”
Section: Resultsmentioning
confidence: 99%
“…Beavis, AL et al (2020) 6 showed low levels of awareness of EH/EC symptoms and low perceived risk may contribute to the low reporting of symptoms. In a study of women presenting for bariatric surgery, half perceived their personal risk of developing uterine cancer as "not likely" or "not possible".…”
Section: Resultsmentioning
confidence: 99%